Airway and peripheral urokinase plasminogen activator receptor is elevated in asthma, and identifies a severe, nonatopic subset of patients. Issue 3 (5th October 2016) - Portelli, M. A.; Moseley, C.; Stewart, C. E.; Postma, D. S.; Howarth, P.; Warner, J. A.; Holloway, J. W.; Koppelman, G. H.; Brightling, C.; Sayers, I.
Abstract: Rationale: Genetic polymorphisms in the asthma susceptibility gene, urokinase plasminogen activator receptor (uPAR/ PLAUR ) have been associated with lung function decline and uPAR blood levels in asthma subjects. Preliminary studies have identified uPAR elevation in asthma; however, a definitive study regarding which clinical features of asthma uPAR may be driving is currently lacking. Objectives: We aimed to comprehensively determine the uPAR expression profile in asthma and control subjects utilizing bronchial biopsies and serum, and to relate uPAR expression to asthma clinical features. Methods: uPAR levels were determined in control ( n = 9) and asthmatic ( n = 27) bronchial biopsies using immunohistochemistry, with a semi‐quantitative score defining intensity in multiple cell types. Soluble‐cleaved (sc) uPAR levels were determined in serum through ELISA in UK (cases n = 129; controls n = 39) and Dutch (cases n = 514; controls n = 96) cohorts. Measurements and main results: In bronchial tissue, uPAR was elevated in inflammatory cells in the lamina propria ( P = 0.0019), bronchial epithelial ( P = 0.0002) and airway smooth muscle cells ( P = 0.0352) of patients with asthma, with uPAR levels correlated between the cell types. No correlation with disease severity or asthma clinical features was identified. scuPAR serum levels were elevated in patients with asthma (1.5‐fold; P = 0.0008), and we identified an association between high uPAR serum levels and severe, nonatopic disease. Conclusions: This study provides novel data that elevated airway and blood uPAR is a feature of asthma and that blood uPAR is particularly related to severe, nonatopic asthma. The findings warrant further investigation and may provide a therapeutic opportunity for this refractory population.